2010
DOI: 10.1016/j.socnet.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring social dynamics in a massive multiplayer online game

Abstract: Quantification of human group-behavior has so far defied an empirical, falsifiable approach. This is due to tremendous difficulties in data acquisition of social systems. Massive multiplayer online games (MMOG) provide a fascinating new way of observing hundreds of thousands of simultaneously socially interacting individuals engaged in virtual economic activities. We have compiled a data set consisting of practically all actions of all players over a period of three years from a MMOG played by 300,000 people. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
264
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(276 citation statements)
references
References 68 publications
10
264
0
2
Order By: Relevance
“…Within this approach in the analysis of online social dynamics data, a variety of social networks were observed in relation with different online activities of users [12,15,16,27,30,[52][53][54][55][56]. Here, we use the accepted methods to construct and analyse the networks from the empirical data from Blogs and Chats; we demonstrate that, although in both systems no a priori associations among users exists and the networks grow starting from scratch, the networks that eventually emerge in these processes belong to two entirely different classes of social structures.…”
Section: Two Classes Of Online Social Network From the Empirical Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Within this approach in the analysis of online social dynamics data, a variety of social networks were observed in relation with different online activities of users [12,15,16,27,30,[52][53][54][55][56]. Here, we use the accepted methods to construct and analyse the networks from the empirical data from Blogs and Chats; we demonstrate that, although in both systems no a priori associations among users exists and the networks grow starting from scratch, the networks that eventually emerge in these processes belong to two entirely different classes of social structures.…”
Section: Two Classes Of Online Social Network From the Empirical Datamentioning
confidence: 99%
“…Recently, intensive research based on these empirical data, seen as examples of complex dynamical systems in the physics laboratory, has been performed: this research contributed to quantitative study of social phenomena on Blogs [10,11], Diggs [12], Forums [13], online games [14,15], online social networks MySpace [16], Facebook [17], Twitter [18], online chats [19] and other online communication systems. By using different machine-learning methods of text analysis (a recent review of methods can be found in [20]), one can infer contents that are communicated in the text messages exchanged between users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On other sites, certain actions can be aggregated and used to infer trust and mistrust. For instance, on Wikipedia, editors are promoted within the administrative structure on the basis of an open vote [75], while some multi-player online games also involve decisions to trust fellow players or not [3,339,340].…”
Section: Trustmentioning
confidence: 99%
“…Viswanath et al studied the structural evolution of the activity network of Facebook and found that the average degree, clustering coefficient, and average path length are all relatively stable over time [6]. Hu & Wang studied the evolution of Wealink [17,18] and found that many network properties show obvious non-monotone feature, including a sigmoid growth of network scale which was also observed by Chun et al in Cyworld [19], and a transition from degree assortativity characteristic of real social networks to degree disassortativity characteristic of many OSNs which was also observed by Szell & Thurner in Pardus [20].…”
Section: Introductionmentioning
confidence: 59%